WHY ISLAMIC EDUCATION NEEDS TO BE INTERNALIZED IN EARLY CHILDHOOD: A QUALITATIVE STUDY OF INDONESIAN PARENTS’ PERSPECTIVES - Firdha Hayati (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2019)
Abstract: The emergence of Islamic education schools has become a trend nowadays in Indonesia. Madrasah Ibtidaiyah, Integrated Islamic Elementary School, Islamic Junior High School and Senior High School, Madrasah Aliyah even Integrated Islamic Kindergarten and Raudhatul Athfal and Aisyiyah Bustanul Athfal (ABA) Kindergarten are widely known among the community. Many parents choose Islamic early childhood education to be their main choice. This study aims to explore why Islamic education needs to be internalized in early childhood. This study was conducted from 19 July 2019 to 20 August 2019 in some cities in Indonesia. A purposeful sampling method was used to select ten eligible participants. Data were collected through face-to-face, semistructured interviews and were analyzed using the conventional content analysis approach. Two categories emerged from the qualitative data including “creating Islamic environment,” and “the program offered is interesting”. According to the results, although the participants decided to choose the Islamic education for their children by selecting the Islamic school, they should consider that they must internalize the Islamic education in family by being role model for their children.